Microwave-assisted enzymatic production of cosmetic ester 2-ethylhexyl oleate and myristate - Eko K. Sitepu; Emilia Abdulmalek; Helmina Sembiring; Rodiah N. Sari; Ella Parawita; Dea Hafizah; Novia Ramadhani; Maya R.S. Siregar; Firman Sebayang; Juliati Br. Tarigan (Case Studies in Chemical and Environmental Engineering)
The enzymatic microwave-assisted cosmetic esters production from esterification of fatty acids with 2-ethylhexanol using enzyme lipase as a biocatalyst was developed. The parameters of enzyme weight, molar ratio, reaction time and microwave power were investigated to determine the maximum conversion of 2-ethylhexyl myristate (EHM) and 2-ethylhexyl oleate (EHO). The maximum conversion of EHM and EHO of 92.0 ± 0.4 % and 98.2 ± 0.3 %, respectively, were achieved under reaction conditions of enzyme weight of 5 wt%, molar ratio of 1:3, reaction time of 0.5 minutes and microwave power of 20 %. All the parameters tested significantly affect the conversion. The reusability test revealed that the liquid lipase lost its catalytic activity after two subsequent cycles. However, the availability of low-cost enzyme lipase derived from genetically modified microorganisms increases its competitiveness. Microwave radiation system has better performance and offers a fast route of cosmetic esters production, which is also more energy-efficient and cost-effective.